2009
DOI: 10.1002/app.29883
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on esterification reactions of starches in 1‐N‐butyl‐3‐methylimidazolium chloride and resulting substituent distribution

Abstract: The ionic liquid (IL) 1-N-butyl-3-methylimidazolium chloride ([C 4 mim] þ Cl À ) was used as solvent for different esterification reactions of the biopolymer starch. Therefore, maize starches with varying content of amylose were used. Different carboxylic acid anhydrides were applied to esterify starch with a degree of substitution (DS) in the range of 0.7-3.0. For example, starch acetates with the mentioned DS are accessible within 30 min at a 105 C-reaction temperature. The DS distribution of starch acetat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…used ionic liquids as solvents for chemical modifications of starch. From then on, more and more studies on ionic liquids used as solvents for starch were reported . However, the facts that the solubility depends on structure of ionic liquids, together with high temperature needed and high cost, greatly restrain their applications in starch industry.…”
Section: Introductionmentioning
confidence: 99%
“…used ionic liquids as solvents for chemical modifications of starch. From then on, more and more studies on ionic liquids used as solvents for starch were reported . However, the facts that the solubility depends on structure of ionic liquids, together with high temperature needed and high cost, greatly restrain their applications in starch industry.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, researchers have reported that starch can be dissolved or plasticized by ILs including 1-allyl-3-methylimidazolium chloride (AMIMCl) (Wang et al, 2009a,b;Wilpiszewska and Spychaj, 2011), 1-butyl-3-ethylimidazolium chloride (BMIMCl) (Lehmann and Volkert, 2009;Liu et al, 2005) and 1-ethyl-3-methylimidazolium acetate (EMIMAc) Budtova, 2013 2013). They found that these liquids disrupt the hydrogen bonding between the hydroxyl groups of starch and damage the original semi-crystalline region, leading to starch dissolution.…”
Section: Introductionmentioning
confidence: 99%
“…Native starch displays high water sensitivity and lack of mechanical strength. Starch can be plasticized to some degree with plasticizer such as water, polyols (glycerol , glycols , xylitol ), amides , or ionic liquids notably. Plasticized starch is biodegradable and is used for packaging and agricultural purposes.…”
Section: Introductionmentioning
confidence: 99%